Social Security as a Developmental Institution? : Extending the Solar Case for the Relative Efficacy of Poor Relief Provisions under the English Old Poor Law /: Extending the Solar Case for the Relative Efficacy of Poor Relief Provisions under the English Old Poor Law. (October 2008) - Smith, Richard Michael, 1946-
No abstract available